2022
DOI: 10.3389/fcell.2022.825247
|View full text |Cite
|
Sign up to set email alerts
|

A Putative Plasmodium RNA-Binding Protein Plays a Critical Role in Female Gamete Fertility and Parasite Transmission to the Mosquito Vector

Abstract: Plasmodium falciparum sexual stage gametocytes are critical for parasite transmission from the human host to the mosquito vector. Mature gametocytes generate fertile male (micro-) or female (macro-) gametes upon activation inside the mosquito midgut. While a number of parasite genes have been described that are critical for P. falciparum gametogenesis and fertility, no parasite gene has been shown to have a unique function in macrogametes. The genome of P. falciparum encodes numerous RNA-binding proteins. We i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 31 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…In contrast, we observed no discernible defect in Pfarid – macrogamete formation. The Pfarid – genetic crosses we performed with transgenic lines producing either fertile microgametes ( 6 ) or macrogametes ( 35 ) confirmed a completely penetrant male defect but, surprisingly, also showed that Pf ARID is required for fertility of female gametes. A recent study describing screening for fertility-related genes in the rodent malaria parasite P. berghei , showed that the P. berghei ARID ( Pb ARID) ortholog named MD4 (PBANKA_0102400) is involved in fertility of male gametes only ( 42 ).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In contrast, we observed no discernible defect in Pfarid – macrogamete formation. The Pfarid – genetic crosses we performed with transgenic lines producing either fertile microgametes ( 6 ) or macrogametes ( 35 ) confirmed a completely penetrant male defect but, surprisingly, also showed that Pf ARID is required for fertility of female gametes. A recent study describing screening for fertility-related genes in the rodent malaria parasite P. berghei , showed that the P. berghei ARID ( Pb ARID) ortholog named MD4 (PBANKA_0102400) is involved in fertility of male gametes only ( 42 ).…”
Section: Discussionmentioning
confidence: 74%
“…To further substantiate the finding that the lack of ARID causes a male-specific defect, we assessed the fertility of male and female Pfarid – gametes using genetic crosses with gene deletion parasite lines which either formed only fertile female gametes ( Pfcdpk4 – ) ( 6 ) or only fertile male gametes ( Pfmacfet – ) ( 35 ). WT Pf NF54, Pfarid – , Pfcdpk4 – , and Pfmacfet – gametocytes were generated in vitro followed by pairwise mixing and fed to female Anopheles stephensi mosquitoes on day 15 of culture.…”
Section: Resultsmentioning
confidence: 99%
“…4 A). We next examined a sex-specific function for Pf HAP2 and Pf HAP2p using genetic crosses with Pfhap2¯ and Pfhap2p¯ parasites in combination with transgenic parasite lines which formed either fertile female gametes only ( Pfcdpk4¯ ) [ 26 ] or fertile male gametes only ( Pfmacfet¯ ) [ 27 ]. WT Pf NF54, Pfhap2¯ , Pfhap2p¯ , Pfcdpk4¯ , Pfmacfet¯ gametocytes were generated in vitro and cultures were first individually fed to A. stephensi mosquitoes on day 15 of in vitro culture.…”
Section: Resultsmentioning
confidence: 99%
“…After determining the role of Pf SRPK1 in male gamete formation, we further analyzed the fertility of male and female Pfsrpk1 − gametes. Since gametocytes in Plasmodium occur together and it is not possible to separate them, we performed genetic crosses between Pfsrpk1 − parasites and transgenic parasite lines, which either formed fertile female gametes only ( Pfcdpk4 − ) ( 8 ) or fertile male gametes only ( Pfmacfet − ) ( 41 ). WT Pf NF54, Pfsrpk1 − , Pfcdpk4 − , and Pfmacfet − gametocytes were generated in in vitro culture for 15 days, and cultures were first fed individually to female A. stephensi mosquitoes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we showed that Pfsrpk1 − parasites did not transmit to the mosquito vector. Utilizing genetic crosses with transgenic parasite lines producing either fertile female ( 8 ) or male gametes( 41 ), we showed that Pf SRPK1 has mainly a male gender function. Female Pfsrpk1 − gametes were fertile, but our observation that their transmission in the cross with the female-deficient line was reduced might indicate some function in females.…”
Section: Discussionmentioning
confidence: 99%